Biodegradable Banana Peels-Based Plastic – A Review - Ab Razak, Siti Noraiza; Yahaya, NA; Rohmadi, R N A; Nordin, N S (Multidisciplinary Applied Research and Innovation, 2020)
This research purposely focused on synthesis of bioplastic material by using banana peels. To achieve the main objective, the properties of bioplastic produced in terms of its strength, chemical compositions, and physical properties is being studied. Bioplastic was prepared by using banana peels as possible replacement to the conventional plastic material. Making bioplastic from banana peels as a substitute for traditional petroleum-based plastic is believed to be a successful key to enhance efficiency of the plastic industry. Glycerol is added as plasticizer which increases its flexibility. To inhibit growth of bacteria and fungi sodium metabisulphite is used. The degradation of bioplastic starts after three to four months from the date of manufacture. The atmospheric condition also affects the degradation period of bioplastic. The result showed that the plastic produced could bear the weight one and half times more than petroleum plastic. Bioplastic film can sustain the weight near about two kilograms, and which have enough tensile strength. The bioplastic prepared from banana peels that can be used as packaging material or as a carrying bag